(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyzes changes that occurred after the introduction of fiscal decentralization in five newly incorporated municipalities in Volyn region in terms of reforming the system of local budgets after year 2016. The changes in the volume of revenue of the budgets joint territorial communities as a result of the reform, and also directions and structure of the implementation of expenditures from budgets are determined. The features and regularities of financial relations of local self-government bodies in the conditions of decentralization the public finances are investigated. The main problems of the created united communities and the procedure and ways of their solution, and also the source of financial resources of each individual project are determined. An analysis of the changes in the provision of united communities by its own resources suggests an increase in its own budget revenues several times, but without state transfer support that exceeds 60 % of the total planned financial resource of the community, implementation of the reform is impossible. Therefore, the financial autonomy of the combined territorial communities is expressed in the reduction of dependence on the redistributive resource from the state budget, part of which is given to the local authorities. But along with this, large areas of established communities and abandoned infrastructure require large investments and attracting investors for special projects.